Strategi Pemberdayaan Pedagang Kaki Lima Di Perkotaan - Endri Bagus Prastiyo; Miswanto Miswanto (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2017)
The presence of street vendors in the corners of the city provides benefits to consumers, government or to traders such as reducing the number of unemployed, as well as providing various community needs at relatively affordable prices. On the other hand, street vendors are often associated with negative impacts on the urban environment with the appearance of dirty, dirty, and disorderly impression. No wonder if people often complain as a result of the activities of street vendors who use public facilities to sell. Community empowerment ideally not only develops the economic potential of the people, but also the dignity, dignity, self-esteem and self-esteem, maintaining the local cultural values. Empowerment as an implementation of socio-cultural concept in people-centered development, not only grow and develop economic added value, but also social value added and added value culture. Non-formal education serves membelajarkan individuals or groups to be able to empower and develop themselves so as to adapt to changes and developments of the times. The first strategy of empowering street vendors is the strategy of directional approach, second strategy is group approach, group approach in empowering street hawkers in urban areas. 4. Strengthening network among street vendors as well as building awareness and network of resources and encouraging active involvement of street vendors